2007
DOI: 10.1002/pds.1469
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization study in a neonatology unit of a tertiary care hospital in eastern India

Abstract: The common diseases for which the neonates sought admission in the NICU were suspected septicaemia, birth asphyxia, neonatal jaundice and major congenital malformations. As antibiotics were the most frequently used drugs, their usage was analyzed in all cases. It was found to be rational in 84% of suspected septicaemia cases, as the provisional diagnosis on admission was confirmed with subsequent investigations thereby justifying appropriate antibiotic therapy. The diagnosis and treatment of other cases like n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
47
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 6 publications
11
47
4
Order By: Relevance
“…This finding was similar to the two studies conducted in eastern and southern India in 2007 and 2011 [12][13][14]. Another study by Smythe et al documented equal number of male and female individuals admitted to the ICU; however, with a significantly higher average age of 65 years [15].…”
Section: Al-zakwani Et Alsupporting
confidence: 88%
“…This finding was similar to the two studies conducted in eastern and southern India in 2007 and 2011 [12][13][14]. Another study by Smythe et al documented equal number of male and female individuals admitted to the ICU; however, with a significantly higher average age of 65 years [15].…”
Section: Al-zakwani Et Alsupporting
confidence: 88%
“…A study reported average number of drugs per encounter as 4.8 which is quiet comparable with our study. 25 Another study reported mean drug usage as 3.6 drugs per infant. 3 However, other studies reported mean drug usage as 7 and 11.1 drugs per neonate respectively.…”
Section: Duration Of Hospital Stay (In Days)mentioning
confidence: 99%
“…Such issues therefore call for a close monitoring of drug prescribing trends in neonates and infants. 5 While prescribing for children's a number of knowledgebased skills and practical considerations are required. 6 Medical personnel providing health care for neonates in developing countries are facing a number of challenges during their day-to-day practice of medicine due to inadequate infrastructure, irregular supply of drugs and other health care facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of antimicrobial agents is vital, its irrational use often leads to emergence and dissemination of drug resistance strains. 5 Drug utilization was defined by the world health organization (WHO) in 1997 as the marketing, distribution, prescription and use of drugs in our society, with special emphasis on the resulting medical, social and economic consequences.…”
Section: Introductionmentioning
confidence: 99%